European Cancer Organisation Essential Requirements for Quality Cancer Care (ERQCC): Lung cancer. (December 2020) - Berghmans, Thierry; Lievens, Yolande; Aapro, Matti; Baird, Anne-Marie; Beishon, Marc; Calabrese, Fiorella; Dégi, Csaba; Delgado Bolton, Roberto C.; Gaga, Mina; Lövey, József; Luciani, Andrea; Pereira, Philippe; et al.
Highlights: European Cancer Organisation essential requirements for quality cancer care (ERQCC) are position papers on delivering high-quality care. Each paper focuses on a cancer type, in this case lung cancer. Lung cancer is a great societal burden and is challenging to treat. High-quality care can only be a carried out in specialised units or centres. The essential, multidisciplinary details for such centres are set out by the European Cancer Organisation expert group. Abstract: European Cancer Organisation Essential Requirements for Quality Cancer Care (ERQCC) are written by experts representing all disciplines involved in cancer care in Europe. They give patients, health professionals, managers and policymakers a guide to essential care throughout the patient journey. Lung cancer is the leading cause of cancer mortality and has a wide variation in treatment and outcomes in Europe. It is a major healthcare burden and has complex diagnosis and treatment challenges. Care must only be carried out in lung cancer units or centres that have a core multidisciplinary team (MDT) and an extended team of health professionals detailed here. Such units are far from universal in European countries. To meet European aspirations for comprehensive cancer control, healthcare organisations must consider the requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis, to treatment, to survivorship.